Phase II single-arm study of brentuximab vedotin in Chinese patients with relapsed/refractory classical Hodgkin lymphoma or systemic anaplastic large cell lymphoma. Issue 9 (2nd September 2021) - Song, Yuqin; Guo, Ye; Huang, Huiqiang; Li, Wei; Ke, Xiaoyan; Feng, Jifeng; Xu, Wei; Miao, Harry; Kinley, Judith; Song, Gregory; Dai, Yi; Wang, Hui; et al.
ABSTRACT: Background: Relapsed/refractory (R/R) classical HL (cHL) and systemic anaplastic large-cell lymphoma (sALCL) treatment options are limited in China. There is a need for new therapies. Research design and methods: This single-arm, open-label, multicenter, Phase II study assessed efficacy, safety, and pharmacokinetics of single-agent brentuximab vedotin in Chinese patients with R/R cHL or sALCL. Patients received brentuximab vedotin 1.8 mg/kg by intravenous infusion on Day 1 of 3-week cycles (maximum 16 cycles). Results: Patients ( N = 39) received a median of 10 cycles (range: 2–16) of brentuximab vedotin. The objective response rate was 69% (95% CI: 52–83%), with 27 patients achieving objective responses (complete response: n = 11 [28%]; partial response: n = 16 [41%]). Median duration of response, progression-free survival and overall survival were 12.1 months, 13.5 months (95% CI: 6.8 months–not estimable) and not reached after a median follow-up of 16.6 months. Brentuximab vedotin was well tolerated with no on-study deaths. AEs were generally manageable and reversible. No new safety signals were identified. Pharmacokinetics were consistent with those previously described in Western populations. Conclusion: Brentuximab vedotin had a positive benefit–risk profile for Chinese patients with R/R cHL or sALCL, confirming it as a potential treatment option. Clinical trial registration: www.clinicaltrials.gov identifier is NCT02939014.